31 Comprehensive cost analysis of inpatient and outpatient heart failure patients – a microcosting approach. (7th October 2015) - Morgan, R; Daly, C; Barry, M
Abstract : Background: In the era of improved care and outcomes of heart failur e (HF) patients the cost of management of such patients is set to rise exponentially. Recently published figures from the HSE reveal an annual rate of HF admissions of 4826 with a resultant annual cost of 25, 917, 762 euro. Aims: 1. To formally assess the cost of inpatient care of HF patients, and to assess the cost of running a Disease Modifying Programme, through the process of microcosting. 2. To compare this cost to (a) Locally derived costs for the same admission, (b) National costs applied to HF admissions and (c) HF costs from the NHS. Methods: Inpatient HF patients were examined at two separate timepoints: 1: patients admitted with HF over 3 years (n = 1196) retrospectively identified through the Hospital In Patient Enquiry (HIPE) record. 2: A second inpatient group (n = 56), admitted and subsequently enrolled on the HF programme. Separate time points were studied to ascertain if the cost of management of HF is increasing over time and whether the implementation of a HF service impacts on this cost. Outpatient heart failure programme (HFP) patients were examined to ascertain the real life cost of running a recently set up HF service. A microcosting exercise was carried out on both groups, as advised by the National Centre for Pharmacoeconomics. Costs were calculated from the perspective of the health service provider. Results: 1196 patients were identified through the HIPE search for HF admissions 2008–2010, mean age 75 years, 52% male. A cardiologist was the primary physician for 1/3 of patients admitted with a primary or secondary diagnosis of HF during this period. AF was the most commonly recorded comorbidity (38%). There was an 11% all cause death rate. HF readmission at 30 days was 9.6%; at 90 days was 16%. Mean length of stay was 17 ± 34 days. Costs are outlined in the Table 1 below. Fifty six patients were enrolled to the HFP in its initial stages. Mean age was 70 years and 58% were male. Two thirds (66%) had known prior CAD. Outpatient Costs: The mean cost of a standard 12 week programme patient was €1063.57. The mean cost per programme for extended programme patients was higher €4710.3 with a median cost of €1206.37. Conclusion: When compared to a microcosting exercise, patient level costing is accurate. In comparison, using DRG costs can significantly underestimate inpatients HF costs. The most expensive component of inpatient HF admissions remains LOS. Mean LOS pre dedicated HFC was 17 (±34) days. Post HFC implementation, mean LOS was 15 (±18) days. There was a significant increase in mean cost of HF admission from 2008–2010 (pre HFC) to 2012 (post HFC) despite the lower LOS. This can be explained by increased utilisation of costly cardiac investigations such as coronary angiography, cardiac MRI, and device therapies such as ICDs or biventricular pacemakers. References: Executive HS. Ready Reckoner. http://www.hse.ie/eng/services/list/1/schemes/cbd/Ready%20Reckoner.pdf UK TDoH. NHS schedule of reference costs 2010/2011 UK NIoCE. Costing statement: Acute heart failure. Implementing the NICE guideline on acute heart failure 2014